Impact of pyrocatechol on the structural, spectroscopic, thermal characteristics, and in vitro bioactivity of gadolinium-enhanced hydroxyapatites - Keser, Serhat; Demirbilek, Fatos; Barzinjy, Azeez A.; Kareem, Rebaz Obaid; Mahmood, Bahroz Kareem; Ates, Tankut; Kaygili, Omer (Elsevier, 2025)
In this study, the effects of pyrocatechol content on the structural, thermal, spectroscopic, and biocompatibility properties of gadolinium (Gd) based hydroxyapatites (HAs) were investigated using X-ray diffraction, Fourier transform infrared spectroscopy, differential thermal analysis, thermogravimetric analysis, and scanning electron microscopy. The results, of this study, show that the energy bandgap (Egap) of Gd-doped HAs decreases to 4.1978 eV, indicating a narrowing of the electronic energy levels compared to pure HAs. The doping of Gd3+ further enhances these effects, as confirmed by enhanced photoluminescence intensity attributed to cooperative energy transfer mechanisms between the dopants. The two most biocompatible materials in the HAs series were determined as 0.42Gd-HA (94%) and P16-0.42Gd-HA (91%). These results demonstrate that even small concentrations of dopant like Gd can meaningfully impact the material's electronic and optical properties, offering potential for its application in areas where a higher bandgap and insulating properties are essential, such as in biomedical implants, coatings, or electronic insulators.
Keywords: Hydroxyapatites (HAs); Gadolinium (Gd); Pyrocatechol; In vitro bioactivity; Biocompatibility; Biomaterials